2008
DOI: 10.1056/nejmoa0800660
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Heart Transplantation after Declaration of Cardiocirculatory Death

Abstract: In three infants awaiting orthotopic cardiac transplantation, transplantation was successfully performed with the use of organs from donors who had died from cardiocirculatory causes. The three recipients had blood group O and were in the highest-risk waiting-list category. The mean age of donors was 3.7 days, and the mean time to death after withdrawal from life support was 18.3 minutes. The 6-month survival rate was 100% for the 3 transplant recipients and 84% for 17 control infants who received transplants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
225
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(233 citation statements)
references
References 14 publications
2
225
0
6
Order By: Relevance
“…The limited human experience to date has been with DCD hearts subjected to relatively short WITs. Boucek et al (27) reported three successful pediatric heart transplants from DCD donors with WITs of 11.5-27 min (mean of 18.3 min). Ali et al (28) reported the reanimation of a human adult heart in vivo following a total WIT of 23 min; postresuscitation, the heart was able to support the donor's circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The limited human experience to date has been with DCD hearts subjected to relatively short WITs. Boucek et al (27) reported three successful pediatric heart transplants from DCD donors with WITs of 11.5-27 min (mean of 18.3 min). Ali et al (28) reported the reanimation of a human adult heart in vivo following a total WIT of 23 min; postresuscitation, the heart was able to support the donor's circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Boucek et al 27 reported successfully transplanting hearts from 3 infant donors in cases of DCD. Some criticized the waiting period of 75 seconds in 2 of the transplants as being too short.…”
Section: Declaration Of Deathmentioning
confidence: 99%
“…6 If this definition is adopted, the use of circulatory support (such as extracorporeal membrane oxygenation or a heart-lung machine) after the declaration of death should, in principle, be prohibited, because circulation would effectively be restored. However, the heart is sensitive to warm ischaemia time, which should prob ably not exceed 15-20 min to protect graft 2,3,7 If heart DCDD is possible, it remains challenging, particularly if circula tory support is not used. Second, the defini tion of death could be based on brain death criteria, 8 but this approach has to be further analysed and discussed.…”
Section: Correspondencementioning
confidence: 99%